2014
DOI: 10.1097/cad.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

Schlafen-11 sensitizes colorectal carcinoma cells to irinotecan

Abstract: Schlafen-11 (SLFN11) showed a highly significant positive correlation with the response of topoisomerase inhibitors in cancer cell lines derived from prostate, lung, etc. However, this finding has not been validated in colorectal cancers (CRCs). Although irinotecan (CPT-11), a topoisomerase inhibitor, is one of the most important drugs in the treatment of advanced and/or metastatic CRC, resistance is a critical drawback to its clinical effectiveness. The present study aimed to investigate the mechanism of SLFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 14 publications
2
45
0
Order By: Relevance
“…In addition, SLFN11 was recently discovered as a dominant response factor of cancer cells to topoisomerase I inhibitors (4, 5). Knockdown of SLFN11 increases chemoresistance of cancer cells to a broad range of DNA damaging agents (4, 6), and ectopic expression of SLFN11 sensitizes colon cancer cells to topoisomerase I inhibitors (7), consistent with the involvement of SLFN11 in the DNA damage response (4). Concurrently, David and coworkers demonstrated an anti-human immunodeficiency virus-1 (HIV-1) function of SLFN11 due to replication inhibition by selective suppression of viral protein synthesis in a codon-usage-dependent manner (8).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, SLFN11 was recently discovered as a dominant response factor of cancer cells to topoisomerase I inhibitors (4, 5). Knockdown of SLFN11 increases chemoresistance of cancer cells to a broad range of DNA damaging agents (4, 6), and ectopic expression of SLFN11 sensitizes colon cancer cells to topoisomerase I inhibitors (7), consistent with the involvement of SLFN11 in the DNA damage response (4). Concurrently, David and coworkers demonstrated an anti-human immunodeficiency virus-1 (HIV-1) function of SLFN11 due to replication inhibition by selective suppression of viral protein synthesis in a codon-usage-dependent manner (8).…”
Section: Introductionmentioning
confidence: 70%
“…Because SLFN11 expression sensitizes cells to DNA damaging agents (4, 5, 7), we tested the impact of EWS-FLI1-mediated SLFN11 expression on the sensitivity of ES cells to camptothecin, a specific topoisomerase I inhibitor whose derivatives irinotecan and topotecan are widely used in the anticancer armamentarium (31). We found that doxycycline-induced EWS-FLI1 down-regulaton significantly reduced the sensitivity of ASP14 cells to camptothecin (IC 50 = 94 nM vs. 17 nM in the presence and absence of doxycycline, respectively; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human SLFN11 has been shown to inhibit viral protein synthesis in HIV-infected cells (32) and to sensitize malignant cells to DNA-damaging agents and other chemotherapeutic cells (15). Human SLFN5 has been implicated in the control of anchorage-independent growth of malignant melanoma cells (18), while human SLFN12 has been im- plicated in the control of differentiation of prostate epithelial cells (13).…”
Section: Discussionmentioning
confidence: 99%
“…There are several human and mouse genes that are members of the SLFN family (9, 11). Prior evidence has implicated members of the Schlafen family in the regulation of tumorigenesis (13)(14)(15)(16)(17)(18). Notably, expression of various members of this family is upregulated following treatment with type I IFNs (17-19), cytokines known to promote induction of antineoplastic, antiviral, and immunoregulatory effects (1-4).…”
mentioning
confidence: 99%
“…Nucleolar RBPs were overrepresented (Supplemental Fig. S1I), including 20 RNA helicases, among which some had previous implications in the DDR, namely DDX5/p68 (Nicol et al 2013), DDX1 (Li et al 2008), SLFN11 (Zoppoli et al 2012;Tian et al 2014), and DDX3X (Sun et al 2013). We thus hypothesized that increased binding of ribosomal proteins and rRNA binders to poly(A) + RNA reflected the DNA damage-induced disruption of nucleoli (Rubbi and Milner 2003).…”
Section: Many Nucleolar Proteins Exhibit Increased Binding To Polyadementioning
confidence: 99%